Gate-tunable resonant Raman spectroscopy of bilayer MoS2 - Lu, Xin (2020)
The gate‐tunable phonon properties in bilayer MoS2 are shown to be dependent on excitation energy. Raman intensity, Raman shift, and linewidth are affected by resonant excitation, while a nonresonant laser does not influence the intensity significantly. The gate‐dependent Raman shift of A1g mode (either blue‐, red‐, or no‐shift) is a result of the combined effect of antibonding electron and resonant‐related decoupling effect. Although the decoupling effect cannot be directly measured due to the resonant background, it can be indirectly and qualitatively probed by observing A1g mode. This study on gate‐tunable resonant Raman spectroscopy has clarified the influence of carrier doping on phonon properties and demonstrates a new degree of freedom in manipulating phonons in 2D material systems.